The neoliberal turn in health: primary care and popular medical clinics on the periphery of São Paulo - Ricardo de Lima Jurca (Geografares, 2022)
This article aims to understand the expansion of the public and private health segment for the management of the population of peripheral territories of the city of São Paulo (South Zone and East Zone). This management is based on the margins of the capitalist peripheral state, seeing the health crisis, from 2020, as an accentuation of the generic elements currently in action in a context of individualization of social policies, thus taking on a social and structural character. In addition to the users interviewed, social leaders and agents of the primary health care program, the Family Health Strategy (ESF) participated in the research. Thus, we seek to privilege the rise of a systemic triage, characterized by neoliberal policies and a health technocracy that has long neglected public health. The SARS-CoV-2 crisis is therefore much more than a health crisis – through different governmental actions and projects, social organizations and institutions and the market – it therefore maintains a close link with the issue of access to popular medical clinics.